Różnice indywidualne w uczeniu się języków obcych w wiejskiej szkole gimnazjalnej - Ellis, Melanie (Neofilolog, 2017)
School achievement in foreign languages is often reported in mean scores, or on normalized scales, where schools are compared with each other and against a national average. This has led to the common belief that rural lower secondary schools in Poland are ‘worse’ than schools in larger centres of population. This paper sets out to demonstrate that such a view is erroneous as it fails to take into consideration the context, either at the level of the school as a whole, or at the level of individual learners. Based on data obtained from the first two years of a large scale longitudinal research project, “Teaching and Learning Foreign languages” (BUNJO 2012, 2013), this case study describes the context of one lower secondary school in a village in the east of Poland and profiles four teenage learners (aged 13-14) who attend this school and their achievement in English over the period of one year.